14C Dating of an Old Wooden Building: Hikobe House in Gunma Prefecture, Japan. Issue 6 (28th December 2017) - Nakao, Nanae; Sakamoto, Minoru; Imamura, Mineo; Ozaki, Hiromasa; Kobayashi, Koichi
Abstract: Hikobe House is an important cultural property located in Gunma prefecture. It is one of the oldest manor houses in the Kanto region of Japan. The age of the Hikobe House has up to now been uncertain. There are no architectural records or memorandum tags that indicate when the Hikobe House was built. The living room of the Hikobe House has a style of the latter half of the 17th century, while the guest rooms exhibit a style more typical of the 16th century. So, architectural historians did not agree when the house was built. The wooden materials of the Hikobe House (zelkova, cherry tree, and Japanese red pine) are species that are not well suited to dendrochronology. Thus we investigated the materials of the Hikobe House using the radiocarbon ( 14 C) dating method. Using both the 14 C wiggle-match dating method on short tree-ring sequences and observations of remodeling traces of the materials, we were able to establish a credible age of Hikobe House as dating from the late 17th century.